The Role of MUI's Fatwa in Influencing the Economic Behavior of Muslims in the Digital Age (Study of Crypto Currency Commerce) - Ziadatur Rohmah; Idah Nur Fajriya Awwalin (PT Justitia Legal Research, 2025)
This research aims to examine the role of the Indonesian Ulema Council (MUI) fatwa in influencing the economic behavior of Muslims, especially in cryptocurrency trading in the digital era. The research method used is descriptive qualitative with data collection through in-depth interviews, observation, and documentation studies of MUI fatwas and related literature. The results showed that MUI's fatwa plays an important role in providing legal certainty and moral guidelines that underlie Muslims' decisions in transacting and investing in cryptocurrency. The fatwa increases the level of trust and awareness of sharia principles, thereby reducing speculative practices and risks that are not in accordance with Islamic teachings. However, the effectiveness of this fatwa also depends on the level of socialization and education to the public. This study concludes that MUI's fatwa is a strategic instrument in shaping the economic behavior of Muslims in accordance with religious values amid the rapid development of digital technology.